Breast cancer - Michell, Michael; Cambridge eBooks (Cambridge : Cambridge University Press, 2010)
Worldwide, breast cancer is by far the most common cancer amongst women, with an incidence rate more than twice that of colorectal cancer and cervical cancer and about three times that of lung cancer. Whilst screening programmes have improved detection, this disease still places a very high burden on healthcare services worldwide. Over the last two decades, improved public awareness, the implementation of population screening by mammography, and the development of new technology for diagnosis have transformed the care of patients with breast cancer. In this volume, recognised experts discuss key current issues in the diagnosis and management of breast disease. The development and application of new diagnostic techniques is described as well as the use of sophisticated drugs for more effective treatment. Complex contentious topics including risk factors, borderline lesions, professional performance and quality assurance are thoroughly explored by an expert multidisciplinary team.
Machine generated contents note: Series foreword; Preface to Breast Cancer; 1. Epidemiology of breast cancer Stephen W. Duffy; 2. Quality assurance in breast cancer screening Roger G. Blanks and Rachel L. Bennett; 3. Measuring radiology performance in breast screening Alistair Gale and Hazel Scott; 4. Advances in X-ray mammography Kenneth C. Young and David R. Dance; 5. Advanced applications of breast ultrasound William Svensson and Victoria Stewart; 6. Mammographic signs of small invasive cancers Michael Michell and Rema Wasan; 7. The radiology of DCIS - current issues Andy Evans; 8. Pathology Sarah E. Pinder and Elena Provenzano; 9. Advanced breast biopsy techniques Robin Wilson and David Evans; 10. Radiological assessment of the axilla Eleanor Cornford and Jonathan James; 11. Breast MRI Fiona Gilbert; 12. Application of PET/CT in breast cancer Iain D. Lyburn and Elizabeth F. Brown; 13. Advances in treatment of breast cancer Muireann Kelleher and Paul Ellis; Index.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Breast -- Cancer -- Imaging; Electronic books